Comparison of the strategies of two opponents in the problem of “conquest” of a territory - Verygina, I. V. (Reports of the National Academy of Sciences of Ukraine, 2016)
The theory of conflict dynamical systems is applied to a model that discribes the conflicting redistribution of a resource space (territory) between adversaries (a pair of opponents).